POLITICAL CULTURE OF SOCIETY AND CONCEPTUAL ISSUES - Yakhshibaev Shavkat (EPRA International Journal of Research and Development (IJRD), 2023)
The problems of political culture as an important category of political science in recent years has become an urgent topic. There are objective and subjective reasons for this, since it is she who is assessed as an important factor influencing the dynamics of the political life of the state and determining their directions. From the same point of view, interests in political culture and its features are increasing, as well as their research directions are developing. The topic manifests itself as a priority and active direction of political science. The article analyzes its regional (eastern and Western) and civilizational foundations and differences.